Chart of the Antarctic continent shewing the icy barrier attached to it discovered by the U. S. Ex. Ex. Charles Wilkes, Esq. Commander 1840 / eng. by Sherman & Smith - United States Exploring Expedition (1838-1842) (United States. Hydrographic Office., 1840)
No. 70. Includes profile views. Grayscale;